PENGARUH METODE PEMBELAJARAN DISKUSI TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA WACHID HASYIM 2 TAMAN SIDOARJO: The Effect Of Discussion Learning Methods On Students' Learning Motivation In Islamic Religious Education Subjects At Sma Wachid Hasyim 2 Taman Sidoarjo - Hidayahtus, Devika; Rodiyah, Siti Kholidatur; Al Chumairoh, Nailul Ulah (STAI Ma'had Aly Al-Hikam Malang, 2025)
This research aims to determine the effect of the discussion learning method on students' learning motivation in Islamic religious education subjects at SMA Wachid Hasyim 2, Taman Sidoarjo. The research method used is quantitative with an Ex Post Facto approach, where the researcher does not manipulate variables. Primary data was obtained from a questionnaire distributed to 119 class XI students, with 9 statement items for the variables of discussion learning methods and learning motivation. Testing the validity and reliability of the instrument using SPSS version 26 shows that all items are valid and reliable. Data were analyzed using simple linear regression and a t-test. The results showed that the discussion learning method had a significant effect on students' learning motivation, with a significance value of 0.000. The coefficient of determination shows that the discussion method explains 40.3% of the variation in learning motivation, while the rest is influenced by other factors, variations in student learning motivation, but there are still other factors that need to be explored further